Elijah's Mantle A Sign of Prophecy Gone Awry - Fetherolf, Christina Marie (2017)
Although Elijah's mantle is typically understood as a symbol of prophetic authority, this article utilizes a narratological analysis to argue that the mantle is instead a sign of Elijah's decline and decommissioning. The function of the mantle in 1 Kings 19 and 2 Kings 2 is examined in order to demonstrate that the mantle is not invested with power and authority. The mantle is instead associated with situations in which Elijah did not perform his prophetic duties in an ideal manner. Descriptions of both Elijah and Elisha elsewhere further reveal that the mantle was not closely related to their identity as prophet, which supports the argument that it was not symbolic of prophetic authority.
Keywords: 1 Kings 19; 2 Kings 2; Elijah; Elisha; mantle; prophetic authority